Investigating the Effects of Combined Pegagan and Snakehead Fish Extracts on BDNF Levels in Rats: Implications for Neuroprotective Therapy - Siregar, Sarah Rahmayani; Surura, Hedya Nadhrati; Lubis, Ilfan Adi Putra; Bukhari, Al (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2025)
One of the most common health problems in the elderly is dementia. People living with dementia were found to have smaller hippocampal volumes and low serum BDNF levels. BDNF increases synaptogenesis, and plays a role in neurogenesis.  It is believed that the decrease in BDNF levels can be prevented by the dietary intake of plants, including gotu kola (Centella asiatica) and snakehead fish (Channa striata). Gotu kola contains  terpenoids and flavonoids, while snakehead fish contains arginine and glutathione. This study aims to examine the combination of water extracts of gotu kola and snakehead fish  as neuroprotector agent. This research was truly experimental; experimental animals (n=35) were divided into seven groups, five animals each with the following treatment: K0: normal control; K-: distilled water 10 mg/kgBW/day; P1: snakehead fish extract 300 mg/kgbb/day; P2: gotu kola extract 300 mg/kgbb/day; P3-P5: combination of gotu kola and snakehead fish at doses of 100/300, 300/300 and 600/300 mg/kgbb/day. The extract is given orally once a day along with induction at K-, P1-P5 with D-galactose (150 mg/kgbb/day) subcutaneously for six weeks. Then, BDNF gene expression was examined in brain tissue using the Real-Time PCR method. Data were analyzed using the One Way Anova test. The results of this study showed that the greatest BDNF gene expression was found in P3 (2.8). This study concluded that a neuroprotective effect based on BDNF gene expression was found in the combination of gotu kola and snakehead fish extracts at a dose of 100/300 mg/kg bb/day